PUBLIC ACCESSIBILITY TO COURT DECISIONS RELATING TO CIVIL DISPUTES IN THE E-COURT SYSTEM - Tiara Rachma Sari; Surahmad (RADJA PUBLIKA, 2025)
This study examines the extent to which the public can access civil dispute decisions through the e-Court system as an implementation of the principle of open trials. Through a normative juridical approach to legal regulations and court decisions, it was found that although e-Court can accelerate and simplify judicial administration, public access to decisions remains unequal. Electronic copies of decisions are only provided to parties directly involved in the case, while the general public or third parties must still submit manual requests or wait for publication in the Supreme Court Decision Directory, which is often not updated quickly and comprehensively. Differences in implementation in each regional court also widen the gap in transparency. The results of this study indicate that the success of e-Court in supporting judicial transparency requires improvements to the publication system and standardization of procedures to ensure more secure and equitable public access to decisions.